Development of Student Worksheets-Based Guided Discovery with a Scientific Approach to Improve Mathematical Connection Ability (Department of Mathematics, Universitas Negeri Semarang, 2022)
The purpose of this study was to develop student worksheets-based on guided discovery with a scientific approach to improve students' mathematical connection ability. The criteria for developing student worksheets are valid, practical, and effective. Type of research is research and development with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were grade 7A junior high school 2 Pulokulon. Data collection techniques include product assessment, questionnaires, observations, and tests. Data analysis techniques include validity test, practicality test, and effectiveness test. The results showed that: (1) the student worksheets met the expert validity with a score of 4.4 and were very good, (2) the student worksheets met practicality with a score of 3.16 with a very good category, and (3) the student worksheets are effective for improving students' mathematical connection ability with classical mastery learning outcomes by 77% and increasing abilities with N-Gain = 0.54 in the medium category.